2018
DOI: 10.1111/1462-2920.14031
|View full text |Cite
|
Sign up to set email alerts
|

Field study reveals core plant microbiota and relative importance of their drivers

Abstract: Summary Harnessing plant microbiota can assist in sustainably increasing primary productivity to meet growing global demands for food and biofuel. However, development of rational microbiome‐based approaches for improving crop yield and productivity is currently hindered by a lack of understanding of the major biotic and abiotic factors shaping the crop microbiome under relevant field conditions. We examined bacterial and fungal communities associated with both aerial (leaves, stalks) and belowground (roots, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
224
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(254 citation statements)
references
References 78 publications
23
224
1
6
Order By: Relevance
“…Here, among those that variables were significant, crop (switchgrass or miscanthus) had the lowest explanatory value ( Table 1 ). However, our work agrees with previous research that has shown a relationship between plant species/genotype and the leaf microbiota of perennial plants such as wild mustard 55 , sugar cane 37 , and tree species like birch, maple, and pine 56 . Time and measured abiotic factors had highest explanatory value ( Table 1 , Table S3 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Here, among those that variables were significant, crop (switchgrass or miscanthus) had the lowest explanatory value ( Table 1 ). However, our work agrees with previous research that has shown a relationship between plant species/genotype and the leaf microbiota of perennial plants such as wild mustard 55 , sugar cane 37 , and tree species like birch, maple, and pine 56 . Time and measured abiotic factors had highest explanatory value ( Table 1 , Table S3 ).…”
Section: Resultssupporting
confidence: 93%
“…Our data suggest a compensatory relationship between members within the Proteobacteria, where members of Gammaproteobacteria and Alphaproteobacteria replace one another over time ( Figure 5A ). Such community transitions have been observed on the phyllosphere of crops such as sugarcane 37 , common beans, soybeans, and canola 38 . A study of endophytic bacteria of prairie grasses, including switchgrass, showed the same trend in abundance of Gamma - and Alphaproteobacteria 52 suggesting that these phyllosphere taxa are facultative endophytes or are similarly affected by the plant development.…”
Section: Resultsmentioning
confidence: 82%
“…These results are consistent with large-scale microbiome studies that identified the core microbiome of different plants like Arabidopsis thaliana [16] or sugarcane [23] and a global soil microbiome study that highlighted that only 500 OTUs account for half of soil microbial communities worldwide [24].…”
Section: Evidences For a Wheat Core Microbiome And Identification Of supporting
confidence: 89%
“…Thus, the olive cultivar seems to influence the establishment of pathobiome communities in olive knots. Accordingly, previous studies have suggested that differences on microbial abundance and diversity between asymptomatic and symptomatic tissues were possibly related to the susceptibility of the plant host to a certain disease 16,[18][19][20][21] . We hypothesized that the detected greater differences in the bacterial composition of OK-susceptible cv.…”
Section: Discussionmentioning
confidence: 99%